2016
DOI: 10.1142/s0219887816300099
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear ordinary differential equations: A discussion on symmetries and singularities

Abstract: Two essential methods, the symmetry analysis and of the singularity analysis, for the study of the integrability of nonlinear ordinary differential equations are discussed. The main similarities and differences of these two different methods are given.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 49 publications
4
59
0
Order By: Relevance
“…In [19], [20] it has been shown that in these case the Lie point symmetries are generated by the special projective algebra and the Noether point symmetries by the Homothetic algebra of the kinetic metric. Similar results have been found for some partial differential equations of special interest in curved spacetimes, as the wave and the heat equation (see [21], [22], [23] and references therein) where it has been shown that in these cases the Lie point symmetries involve the CKVs.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…In [19], [20] it has been shown that in these case the Lie point symmetries are generated by the special projective algebra and the Noether point symmetries by the Homothetic algebra of the kinetic metric. Similar results have been found for some partial differential equations of special interest in curved spacetimes, as the wave and the heat equation (see [21], [22], [23] and references therein) where it has been shown that in these cases the Lie point symmetries involve the CKVs.…”
Section: Introductionsupporting
confidence: 80%
“…We conclude that the Bianchi III spacetime ds 2 (III) = e mλτ A 2 (τ ) −dτ 2 + dx 2 + e −mτ dy 2 + e −mλτ e −2x dz 2 (22) admits the proper CKV L 1 with conformal factor ψ (III) (L 1 ) = 2 m A,τ A + λ which reduces to a HV when A (τ ) is an exponential in which case the line element is ds 2 (III) = −e mκτ dτ 2 + e mκτ dx 2 + e m(κ−1)τ dy 2 + e m(κ−λ)τ e −2x dz 2 (23) or in equivalent form…”
Section: Case γ 2 (τ ) = E Mτmentioning
confidence: 68%
“…One can see that the above equation is invariant under time translations. For that if we select H = v and dH/dt = W (v), then the differential equation becomes the first order Abel equation of the second type: W W v + AW + Bv 2 + Cv + D = 0, where W v = dW/dv, and its solution in general cannot be written in a closed form expression, for more discussions see [38]. Thus, in the following we we shall consider several models starting from the simplest to the complex one and their physical consequences as well.…”
Section: Model 2: λ(Hḣḧ)mentioning
confidence: 99%
“…Since α is unrestricted, thus we consider two separate cases, namely, α < 0 and α > 0. Now, solving the equation (38) for α < 0, one finds that the Hubble factor evolves as > 0 as H 0 > 0. The scale factor is can be solved as…”
Section: The Model λ(ḣ) = α + µḣmentioning
confidence: 99%
“…Two of the most famous are: (a) the existence of invariant transformations, i.e. symmetries and (b) the singularity analysis; for a recent discussion and comparison of these two methods see [10]. Both of these have been applied widely in gravitational theories [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%